Tissue oxygen saturation as an early indicator of delayed lactate clearance after cardiac surgery: a prospective observational study. Issue 1 (December 2015) - Kopp, Rüdger; Dommann, Katja; Rossaint, Rolf; Schälte, Gereon; Grottke, Oliver; Spillner, Jan; Rex, Steffen; Marx, Gernot
Abstract Background In this observational study near infrared spectroscopy (NIRS) was evaluated as a non-invasive monitor of impaired tissue oxygenation (StO2 ) after cardiac surgery. StO2, cardiac output, mixed venous oxygen saturation and mean arterial pressure were compared with lactate clearance as established measure for sufficient tissue perfusion and oxygen metabolism. Methods Forty patients after cardiac surgery (24 aortocoronary bypass grafting, 5 heart valve, 3 ascending aorta and 8 combined procedures) were monitored until postoperative day 1 with NIRS of the thenar muscle (InSpectra™ StO2 -monitor, Hutchinson Technology), a pulmonary-artery catheter and intermittent blood gas analyses for the assessment of lactate clearance. Results StO2 was reduced 4 h after surgery (75 ± 6 %), but recovered at day 1 (84 ± 5 %), while lactate concentration remained increased. Using uni- and multivariate regression analysis, minimum StO2 (r  = 0.46, p <0.01 ) and cardiac index (r  = 0.40, p <0.05 ) correlated with lactate clearance at day 1, while minimum mixed venous saturation and mean arterial pressure did not. In a receiver-operating characteristics (ROC) analysis, minimum StO2 (with a threshold of 75 %) predicted a lactate clearance <10 % at day 1 with an area under the ROC-curve of 0.83, a sensitivity of 78 % and a specificity of 88 %. In the subgroup with StO2  < 75 %, troponin and creatine kinase MB were significantly increased at day 1. Conclusions StO2 below 75 % in the first hours after surgery was a better early indicator of persistent impaired lactate clearance at day 1 than cardiac index, mixed venous oxygen saturation or mean arterial pressure.